Documenting Disappearance: Personal Archives, Life Writing, and the Self in Sri Lanka - Aton, Henria (Archivaria)

(untitled) (Association of Canadian Archivists, 2022)
On August 12, 2022, Tamil relatives of those forcibly disappeared during the Sri Lankan Civil War (1983–2009) marked their 2,000th day of public protest. Since these roadside protests began, elderly women and men searching for their loved ones have passed away and transitional justice promises have failed, but the disappeared have not been found. This article examines archives of the disappeared: collections of files, objects, photographs, etc. about missing loved ones. Paradoxically, these archives, as evidence that the disappeared once lived, are at the core of the protests, yet they are still overlooked by the Sri Lankan state. I explore these collections by examining the intersection of critical personal archives, life writing scholarship, and South Asian studies. The emerging field of critical personal archives suits the unique quality of archives of disappearance, their constructed nature, and their underlying intimacy. Life writing scholarship focuses a much-needed critical lens on self-representation, power, and narrative in archives, especially regarding those whose stories are marginalized and/or not deemed archivable. Drawing on semi-structured interviews I carried out with mothers of the disappeared in 2016–2017 and 2022, I analyze these archives using three life writing concepts: relationality, cultural scripts, and autotopography. The result reaffirms the enduring cultural, political, and personal value of archives of the disappeared and calls for reimagining personal archives as politically and emotionally powerful forms of representation that carve space for love and resistance.